Risteard O Glaisne (1927-2003): Scribhneoir, beathaisneisi, iriseoir, craoltoir, muinteoir agus gaeilgeoir - ni Ghormain, Caoimhe (Trinity College Dublin, 2007)
Born in Bandon, Co. Cork in 1927, Risteard O Glaisne was educated at Bandon Grammar School and Trinity College, Dublin. He is best known in Irish-speaking circles for his books on such diverse subjects as Dr Ian Paisley, Dr Conor Cruise O'Brien, Cardinal Thomas O Fiaich and Irish Methodism. One of his most remarkable achievments as founder-editor was the successful launch in 1958 of Focus, an inter-denominational Protestant review. Amongst his papers are letters from writers such as Mairtin O Chadhain, Ciaran O Nuallain, Sean O Riordain, Gabriel Rosenstock and Nuala Ni Dhomhnaill; material relating to O Glaisne's works, published and unpublished; and material concerning organisations with whom O Glaisne was involved between the early 1940s and 2003, such as Moral Re-Armament, the Anti-Apartheid movement and Amnesty.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Risteard O Glaisne; Irish language activism; Twentieth-century Irish history; Irish literature; Manuscripts Collection, Trinity College Library Dublin